Korrelation zwischen diagnostischer Bildgebung und Entzündungsparametern bei Sakroiliitis - Şan, Hüseyin; Şan, Ayça Uran (Aktuelle Rheumatologie, 2021)
Objectives Sacroiliitis is an inflammation of the sacroiliac joints. Diagnostic imaging has a very important role in the diagnosis of sacroiliac involvement in the disease process. In addition, laboratory parameters can also be useful for the detection of inflammation. This study aims to investigate the relationship between active sacroiliitis and subclinical inflammation parameters in patients who underwent MRI and 99mTc-methylene diphosphonate (MDP) bone scintigraphy.Material and Methods This study includes 65 patients with suspected spondyloarthritis (SpA). Patients who had a sacroiliac MRI, a 99mTc-MDP bone scintigraphy and a complete blood count (CBC) within 3 months were reviewed retrospectively. Sacroiliac joints were evaluated bilaterally by using bone scintigraphy and MRI. Blood inflammation parameters were further assessed regarding evidence of probable sacroiliitis.Results Significant differences were reported between MRI groups for sacroiliac indices (SII) (p=0.003), neutrophil-to-lymphocyte ratio (NLR) (p=0.008), C-reactive protein (CRP) (p = 0.037), and white blood cell (WBC) count (p=0.031). A significant correlation was found between active sacroiliitis and SII (p=0.001), CRP (p=0.000), erythrocyte sedimentation rate (ESR) (p=0.000), and NLR (p=0.001). Based on the ROC curve analysis, SII was found to have a sensitivity of 64.3% and specificity of 69.8%; NLR was found to have a sensitivity of 64.3% and specificity of 73.3% for diagnosing active sacroiliitis.Conclusions Subclinical inflammation indices obtained from CBC and, particularly, NLR may contribute to disease activity assessment like acute-phase reactants. However, this needs to be confirmed in further studies.
Keywords: sacroiliitis; neutrophil-to-lymphocyte ratio; magnetic resonance imaging; scintigraphy